Kazakhstan - On the Crest of the Oil Wave : Kazakhstan Economic Update, Spring 2013 - Sarsenov, Ilyas; Madani, Dorsati (World Bank, Washington, DC, 2015)
Economic growth slowed in 2012 due to capacity constraints in the oil sector, weaker global demand for metals, and unfavorable weather conditions affecting crop production. Overall, industrial output expanded by 0.5 percent in 2012, with negligible contribution to Gross Domestic Product (GDP) growth for the year. Against the decline of agriculture, and little change in industry overall, real GDP growth was supported by a 10 percent year/year growth of the services sector in 2012. Higher export revenues supported strong domestic demand for trade and transportation, as well as for other non-tradable services. High oil prices continued spurring domestic consumption while fixed capital investments remained depressed. Private consumption remains the main contributor to GDP growth as it has been growing by 9-10 percent a year since 2010, supported by favorable commodity prices and high oil export revenue. Exports of oil largely influence the composition of Kazakhstans trading partners, while membership in the customs union appears to be affecting composition of imports. The European Union (EU) maintains the first place among trading partners of Kazakhstan, mainly due to large imports of oil and other mineral resources from Kazakhstan. Overall, employment creation continues to be driven by the services sector. Kazakhstan growth has been pro-poor, driven by job creation and real income gains. However, income disparity, which had improved up to 2009, has worsened slightly due to the crisis.